USE OF BOTULINUM TOXIN TYPE A (BOTOX) AND ITS AESTHETIC BENEFITS - Fernandes de Sousa, Suely; Caroline de Souza, Anne; Silva Oliveira, Geane; Braga Rolim Vieira, Renata (Health and Society, 2023)
The skin is the most external organ responsible for protecting the innermost layers of the body, protecting it against thermal agents, climate change and other organic defenses in relation to the environment. Human development is marked by several natural processes within the body itself, however, skin aging is a factor that occurs intrinsically or extrinsically, leaving the appearance of wrinkles and expression lines visible. The use of botulinum toxin type A (TBA or Botox) has been carefully used for aesthetic purposes in the treatment of discomfort resulting from facial skin aging. The present study aimed to present the aesthetic benefits of using botulinum toxin - Botox. This is an integrative review of the literature using the National Library of Medicine (PubMed) and Virtual Health Library (VHL) databases with the search for articles using the descriptors “botulinum toxin”; “aesthetics” and “facial aging” registered in DeCS with the help of the boolean operator and. The selection of articles was carried out using the inclusion criteria where articles from the last five were selected, in Portuguese or foreign language and which were correlated with the main theme of the research. For the exclusion criteria, articles that were not consistent with the theme and duplicate articles were excluded by title or abstract. Thus, the present study aimed to achieve the objectives described through literature review analysis, where it was possible to verify the effectiveness and benefits of TBA in the facial aging process. Furthermore, it was possible to enable scientific research as a development for further studies in the area of aesthetics in general and contributing to a greater collection of knowledge.